A Network Effects Model of Charisma Attributions - Pastor, Juan-Carlos; Meindl, James R.; Mayo, Margarita (Academy of Management Journal, 2002)
We propose a network effects model of charisma that specifies the distribution and change of charisma attributions among individuals connected in a social structure. Data from a police organization and a classroom setting were analyzed using social network methods. The results show that social network parameters are significantly associated with the distribution and dispersion of attributions of charisma. Results are discussed in terms of their theoretical significance for understanding the socialized aspects of charisma attributions.